2007
DOI: 10.1128/mcb.00692-07
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Bromodomain Protein, FSH-S, Activates the Homeotic Gene Ultrabithorax through a Critical Promoter-Proximal Region

Abstract: More than a dozen trithorax group (trxG) proteins are involved in activation of Drosophila HOX genes. How they act coordinately to integrate signals from distantly located enhancers is not fully understood. The female sterile (1) homeotic (fs(1)h) gene is one of the trxG genes that is most critical for Ultrabithorax (Ubx) activation. We show that one of the two double-bromodomain proteins encoded by fs(1)h acts as an essential factor in the Ubx proximal promoter. First, overexpression of the small isoform FSH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 67 publications
4
64
0
Order By: Relevance
“…Moreover, we identified a Pc-interacting protein called Fs(1)h that might, as well, contribute to recruitment of PRCs to chromatin. Fs(1)h interacts strongly with Ubx, trx, and ash1 mutations and leads to homeotic phenotypes when overexpressed (20). Fs(1)h is essential for development and conserved in mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we identified a Pc-interacting protein called Fs(1)h that might, as well, contribute to recruitment of PRCs to chromatin. Fs(1)h interacts strongly with Ubx, trx, and ash1 mutations and leads to homeotic phenotypes when overexpressed (20). Fs(1)h is essential for development and conserved in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Fs(1)h was previously reported to bind to Zeste motifs upstream of the Ubx gene supporting Ubx expression (20). Another protein with a putative DNA-binding domain is the histone acetyltransferase (HAT) Enoki mushroom (Enok) of the MYST family.…”
Section: Purification Of Pc-bio Reveals Previously Undescribed Interamentioning
confidence: 99%
“…The fact that BET domain proteins Bdf2 in fission yeast and Bdf1 in budding yeast regulate heterochromatin spreading suggests that BET inhibitors may affect the spreading of heterochromatin and reset the epigenetic landscape in cancer cells. In other multicellular organisms such as zebrafish, worms, and flies, BET proteins are essential for the determination of cell fate during development (Huang and Dawid 1990;Chang et al 2007;Dibenedetto et al 2008;Shibata et al 2010). In particular, the Drosophila BET protein FSH (female sterile 1 homeotic) is classified as a Trithorax group gene that counteracts Polycomb group protein-mediated gene silencing (Chang et al 2007;Kockmann et al 2013).…”
Section: Implications Of Bet Protein Functions In Other Systemsmentioning
confidence: 99%
“…In other multicellular organisms such as zebrafish, worms, and flies, BET proteins are essential for the determination of cell fate during development (Huang and Dawid 1990;Chang et al 2007;Dibenedetto et al 2008;Shibata et al 2010). In particular, the Drosophila BET protein FSH (female sterile 1 homeotic) is classified as a Trithorax group gene that counteracts Polycomb group protein-mediated gene silencing (Chang et al 2007;Kockmann et al 2013). Thus, it seems that the function of BET proteins in antagonizing gene silencing is highly conserved across species.…”
Section: Implications Of Bet Protein Functions In Other Systemsmentioning
confidence: 99%
“…Further, Pho-binding sites alone are not sufficient for PcG recruitment; rather, PREs consist of a collection of binding sites for many proteins (5). Other DNA-binding proteins implicated in PRE activity include Spps (Sp1 factor for pairing-sensitive silencing), GAF/psq (GAGA factor/pipsqueak), Zeste/fs(1)h [female sterile (1) homeotic], Grh (Grainyhead), Dsp1 (dorsal switch protein 1), and Adf1 (alcohol dehydrogenase transcription factor 1) (25)(26)(27)(28)(29). Genome-wide studies have shown that many of these proteins are present at only a subset of PREs, suggesting diversity in PcG protein-complex recruitment.…”
mentioning
confidence: 99%